Mandatory minimum contributions, heterogenous endowments and voluntary public-good provision - Claudia Keser; Andreas Markstädter; Martin Schmidt (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
In a public-good experiment with heterogeneous endowments, we investigate if and how the contribution level as well as the previously observed "fair-share" rule of equal contributions relative to ones endowment (Hofmeyr et al., 2007; Keser et al., 2014) may be influenced by minimum-contribution requirements. We consider three different schedules: FixMin, requiring the same absolute contributions, RelMin, requiring the same relative contributions, and ProgMin, requiring minimum contributions that progressively increase with the endowment. We find that minimum contributions exert norm-giving character and may lead to an increase in average group contributions. This is especially true for the progressive schedule. On the individual level, this schedule leads to higher relative contributions by the wealthier players and thus violates the "fair-share" norm. On the group level, it leads to highest contribution level and the lowest inequality in total profits as measured by the Gini index.
Keywords: C92; D63; H41; 330; experimental economics; public goods; heterogeneous endowments; mandatory minimum contributions; norms